Understandings in Local Government, Educational Grant Procedure of Small Schools with 60 Students or Less in Ratchaburi’s Primary Educational Service Area 1 - สุยะหลาน ปรีชา; ชวลิตธำรง กิ่งกนก (Thai Interdisciplinary and Sustainability Review, 2019)
The purposes of this research were to study the understandings of small schools with less than 60 students in the procedure of educational grants from local governments. It is also set to find out the problems and obstacles of such procedure and to set up a guidance of grant procedure. This research is Qualitative using focus group discussion and in-dept interview and documentary research from secondary sources such as official documents, textbooks, reports and scholarly journals. The results have shown that the small schools in Ratchaburi’s Primary Educational Service Area 1 misunderstand the procedure to the cancellation of previous one. Furthermore, those schools have not consistently been informed whenever there are such changes. The local governments themselves never set up a precise framework and timeline for such procedure. This results in insufficient educational budget for those small schools.